Manajemen Dakwah dalam Perspektif Al-Quran - Tri Handayani , Nur Annisa; Jama, Haki Algifari (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2024)
The era of globalization presents new challenges for da'wah, such as the obscuring of religious identity and religious radicalization. This context demands that da'wah not only serve as an act of ubudiyyah but also as a professional implementation relevant to contemporary needs. This study aims to analyze the management principles in the Qur'an and their application in modern da'wah, particularly through digital media. The method used is a descriptive approach with library research, focusing on the analysis of da'wah-related verses and management principles. The findings show that the Qur'an encompasses management principles such as planning, organizing, directing, and controlling, which can be applied in da'wah activities to achieve effectiveness and efficiency. In the digital era, da'wah can be conducted through meticulous planning, organizing involving technology experts, execution via digital platforms, and data-driven control. This study concludes that management-based da'wah derived from the Qur'an can be an effective solution to address the challenges of the modern era. The contribution of this research lies in emphasizing digital media-based da'wah methods grounded in Islamic management principles, which expand the reach of da'wah, enhance relevance, and maintain alignment with Qur'anic teachings